(untitled) (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
A comparative study was conducted to detect blood metabolic biomarkers of show and racehorse stallions in Iraq. Five stallions were selected for each, and blood samples were collected via jugular venipuncture twice a time, fourteen days apart. Amino, fatty, carboxylic, and non-esterified fatty acids were investigated. Some hematological and biochemical attributes were also studied for show and racing stallions. All essential amino acids (except for threonine), non-essential amino acids (except for glutamine, glycine, and isoleucine), white blood cell (WBCs) count, granulosa (GR) percentage, and alkaline phosphatase (ALP) activity were higher (P≤0.05) in racing compared to the show stallions. On the other hand, more significant (P≤0.05) percentages of lymphocytes (LY), platelets (PLT), fatty acids concentrations, acetic acid concentration, and non-esterified fatty acid (NEFA) concentration were observed for show than racing stallions. In conclusion, some blood metabolites and biomarkers differed between show and racehorse stallions. These are of utmost importance for monitoring the nutritional and metabolic alterations, and accurate decisions could be issued to select them earlier for multipurpose purposes.